The influence of entrepreneur orientation and government role toward batik SMES performance in the Pacitan - Sudjatno, Sudjatno; Safitri, Rini (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
This research has aim to determine the effect of entrepreneur orientation on performance of existing businesses in SMEs Batik Pacitan District and the government role as mediating variable. Questionnaire was used to collect data and this research called explanatory quantitative research. The sample is the amount of 40 respondents in the Pacitan that is work in the Batik SMEs. To analyse the data used Warp PLS. This research gives correlation evidence between entrepreneur orientationÂ and business performance. The R square score in the amount of 0.64, that means regression model able to explain 64% the effect of government role to the entrepreneur orientation toward business performance and the 36% for the rest will be explained by other varible that exclude this research. Based on that result, the goverment should pay attention to the entrepreneur and give contribution to them for expand SMEs because it will give feedback to the government for example increase per capita income, opening job vacancy, and reduce unemployment.Â Â